International Journal of Management, Economic and Accounting Volume 3, Issue 5 October 2025 E-ISSN 3025-5627 (Online) https://doi.org/10.61306/ijmea - Shela Oktaviana; Emi Masyitah (International Journal of Management, Economic and Accounting, 2025)
Tax reporting is an administrative obligation that must be carried out by taxpayers and tax withholding taxpayers in order to convey tax information to state authorities. In the banking sector, tax reporting on deposit and savings interest plays an important role as a form of transparency as well as a form of compliance with tax regulations. This study aims to analyze the application of taxes on deposit and savings interest as well as the level of tax reporting compliance at PT Bank Sumut KCP Brayan Medan. In addition, this study also examines the obstacles faced by banks and customers, efforts that have been made to improve compliance, and customer perceptions of these tax obligations. The research uses a qualitative approach with data collection techniques in the form of in-depth interviews, observations, and documentation. The data obtained was analyzed with the help of NVivo software to find the main themes related to tax compliance. The results of the study show that tax reporting has been carried out in accordance with the provisions through the e-Bupot system with an automatic deduction of 20% on deposit and savings interest. However, implementation still faces obstacles in the form of limited human resources, technical problems, and sudden regulatory changes. From the customer side, there is a lack of understanding and a lack of socialization, which causes a perception of lack of transparency. Therefore, tax reporting compliance will be optimal if there is a synergy between strengthening the bank's internal system and improving communication, transparency, and education to customers.